برنامج الطلاقة بالعربية ستين يومابدار اللغة العربية - Fitriani, Intan; Ninoersy, Tarmizi; Mubshirah, Dara (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2020)
Darul Lughah Al Arabiyah is an institution focused on language training and language proficiency development. Darul Lughah Al Arabiyah offers many programs, one of which is a 60-day program fluent in Arabic. The 60-day fluent Arabic program is an intensive program in four or six hours of study per day from the first book to the third of the al-arabiyah baina yadaik books. The purpose of this research is to find out the learning process of the 60-day program fluently speaking Arabic. The research method used is a descriptive method. The data and information for this study was collected by interviewing with the director and teacher at Darul Lughah Al Arabiyah, then with live observation data during the learning process, finally by looking at the documents. And the results of this study, that the 60-day program fluently speaks Arabic using direct methods and its learning focuses on language training and development, and requirements when the arabic language learning process is done well and in accordance with the criteria of arabic language learning.